The mechanism of age-related immunity in cattle - Sharma, Parul (2019)
The present study attempted a cellular and transcriptomatic approach to investigate the age-related immune response in cattle during intra-cellular protozoan infection. Neospora caninum is an obligate intracellular protozoan parasite that causes abortion and negative economic impacts in cattle worldwide. It is important to understand the protective immune mechanisms in response to N. caninum infection and develop an effective and safe vaccine for cattle. There are limited studies available that directly address the age-related immune difference during N. caninum. The immune response during N. caninum infection is Th1 based and mediated by high expression of pro-inflammatory cytokines; most importantly interleukin 12 (IL-12), interferon gamma (IFN-γ) and nitric oxide (NO) by immune cells predominantly macrophages. Monocytes are pivotal due to the link they form between the innate and adaptive immune response and are one of the first immune cells encountered by intra-cellular parasites during infection.